Effects of a 10% carbamide peroxide bleaching agent on rat oral epithelium proliferation - Albuquerque Rodrigo de Castro; Gomez Ricardo Santiago; Dutra Rodrigo Aliprandi; Vasconcellos Wallison Arthuso; Gomez Renato Santiago; Gomez Marcus Vinícius (Brazilian Dental Journal, 2002)
The purpose of the present study was to evaluate the influence of short course topical application of carbamide peroxide on proliferating cell nuclear antigen (PCNA) immunohistochemical expression in the oral tongue mucosa of rats. Twelve male Wistar rats were submitted to topical application of 10% carbamide peroxide on one side of the dorsal tongue once a week for three consecutive weeks. Only distilled water was applied on the control side. The animals were killed on days 0, 10, and 20 after the last application. The tongue was fixed in buffered formalin for 24 h and embedded in paraffin. Tissue blocks (3 µm) were subjected to the biotin-streptavidin amplified system for identification of PCNA. The percentage of epithelial-positive basal cells in each side of the tongue mucosa was calculated. The results demonstrated that topical application of 10% carbamide peroxide increases PCNA immunohistochemical expression on the basal layer of the oral mucosa epithelium of rats on day 0 after treatment. In conclusion, short-course use of carbamide peroxide induces transient epithelial cell proliferation of the oral mucosa of rats.